Global mountain cinema - Fuchs, Michael; Gunning, Tom; Haque, Kamaal; Haque, Kamaal; Höbusch, Harald; Liu, Mia Yinxing; Marini, Anna Marta; Mehrbrey, Sophia; Mossner, Alexa Weik von; Müller, Eva-Maria; Peabody, Seth; Poole, Ralph J.; et al. (Edinburgh University Press, 2025)
The first academic book to approach mountain film culture from transgeneric, transnational, ecotritical, and transmedial perspectives Reconsiders the legacy of the mountain film by exploring mountains as sites of cinematic innovation across a variety of genres and aesthetic traditionsTraces cinematic production routes from Europe to Asia, the United States, and South America, moving beyond generic and national confines toward a transnational history of mountain cinemaAnalyzes the diverse and wide-ranging cinematic strategies used to depict the human impact on mountain environmentsExamines how mountainous ‘reinventions of cinema’ remediate environmental awareness and understandingThis book is dedicated to the particular challenges and opportunities mountains raise for histories and theories of cinema. In German-speaking countries, the relationship between mountains and cinema has been largely reduced to a small canon of Alpine filmmakers whose work has been categorized as the Classical Bergfilm. However, from a transnational and transgeneric perspective, the field of mountain cinema is not only much richer and more diverse, but also addresses questions that are vital to film and media studies and inform postcolonial and environmental discourses in the Anthropocene. In this vein, our volume goes beyond national contexts to provide a timely and much-needed investigation into the generic innovations and intersectional negotiations of national, ethnic, and gender norms that take place in mountain cinema and its related media forms